Penerapan Force Majeure dalam Pemenuhan isi Kontrak Akibat Pandemi Covid-19 di Indonesia - Parwati, Desak Nyoman Dwi Indah; Sarjana, I Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
This study aimed to analyze the application of force majeure related to the fulfillment of contract contents in contracts due to the covid-19 that occurred in Indonesia. Normative legal research was the method chosen in this study. The result of study indicated that has been performed display that with the issuance of Presidential Decree No. 12 of 2020 concerning Determination of Non-Natural Disasters for the Spread of Corona Virus Disease 2019 by some people as a legal basis for determining covid-19 as force majeure. Debtors are allowed to submit to creditors that the Pandemic Covid-19 has made debtor difficult for to fulfill the contents of the contract. However, not all debtors can use Covid-19 as an excuse for force majeure, only debtors who do not have a steady income and are proven directly to creditors who can use the Covid-19 excuse as force majeure and good faith is needed from the debtor. In addition, related to the impact of force majeure on the fulfillment of the contents of the contract in a contract being disrupted, the process of fulfilling the contents of the contract is delayed due to the covid-19 pandemi but does not make a contract void or can be canceled. Penelitaian ini bertujuan untuk menganalisa mengenai penerapan force majeure terkait pemenuhan isi kontrak dalam kontrak akibat pandemi covid-19 yang terjadi di Indonesia. Penelitian hukum normative merupakan metode yang dipilih dalam penelitian ini. Hasil penelitian menunjukkan bahwa dikeluarkannya kebijakan tentang Penetapan Bencana Non-Alam Penyebaran Corona Virus Disease 2019 melalui Keppres No. 12 Tahun 2020 oleh sebagian masyarakat dijadikan acuan dasar hukum penetapan covid-19 sebagai alasan force majeure. Debitur diperbolehkan mengajukan kepada kreditur bahwa adanya pandemi covid-19 menyebabkan debitur sulit untuk memenuhi isi kontrak. Namun tidak semua debitur bisa menggunakan covid-19 sebagai alasan force majeure, hanya debitur yang tidak memiliki penghasilan tetap saja dan dibuktikan langsung kepada kreditur yang bisa menggunakan alasan covid-19 sebagai force majeure serta diperlukan adanya itikad baik dari debitur. Selain itu terkait dengan dampak force majeure terhadap pemenuhan isi kontrak dalam suatu kontrak menjadi terganggu, proses pemenuhan isi kontrak menjadi tertunda akibat pandemi covid-19 namun tidak menjadikan suatu kontrak menjadi batal atau dapat dibatalkan.